EXAMINING PUBLIC SATISFACTION OF LOMBOK TENGAH REGENCY CIVIL REGISTRY SERVICE OFFICE ADMINISTRATIVE SERVICE BASED ON GOVERNMENT SYSTEM - Ida Surya (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
ABSTRACT. Public service is something that needed by the public. So in this regard, the government as an official public body has the duty and responsibility to provide the best service to the public itself. But the efforts made as a public service provider do and work, certainly not able to provide satisfaction to the public itself. Satisfaction with a service is one of the rights that obtained by someone.